The influence of late retirement on health outcomes among older adults in the policy context of delayed retirement initiative: an empirical attempt of clarifying identification bias - Jiannan Li; Bocong Yuan; Junbang Lan (BMC, 2021)
Abstract Background The deepening population aging is urging policy makers to launch delayed retirement initiative, when the society is faced with unprecedented challenges of shrinking labor supply, heavier pension burdens and slowing economic growth. However, the health outcomes of late retirees receive scarce attention due to the intrinsic identification difficulties (i.e., (1) self-selection bias - older adults with predetermined ill-health are less likely to delay retirement. (2) there can be situations where the status of late retirement has terminated at the time of interview, although he/she has ever delayed retirement). To fill in this research gap, this study examines the effect of late retirement on the difficulty in physical functioning and problems of cognitive status among older adults. Method Using the data from China Health and Retirement Longitudinal Study (CHARLS-2015 harmonized, and CHARLS-2018), this study investigates the influence of late retirement (year 2015) on the difficulty in physical functioning and problems of cognitive status (year 2018) among older adults. A series of robustness checks are also conducted. Results Empirical results show that late retirement is associated with better physical functioning and cognitive status. The influence remains robust after considering potential self-selection bias and the sensitivity of including/excluding older adults who have past late retirement experience but have no longer been late retirees at the time of survey. Conclusion This study suggests that older adults might benefit from the engagement in late careers in their physical and cognitive functioning.